LATAR ARKEOLOGIS DALAM NOVEL PENGUASA-PENGUASA BUMI KARYA DON RICHARDSON - Lestari, Ummu Fatimah Ria (BALAI ARKEOLOGI PAPUA, 2011)
This paper discusses about the archeologist settings on Penguasa-Penguasa Bumi novel that written by Don Richardson. This novel tells about Stan Dale and Yale people. Stan Dale is a missionary on Papua. He was effort to introduce the Jesus ’ rule in Yale’s life. This is a description method and the technique of this research is library research. The result of this research is to find most of the Dokwi Vam, Kuil Kembu, Yogwa, and Seimima on its archeologist setting.